CODEX THEODOSIANUS: THE FIRST STATE CODIFICATION OF THE ROMAN ORDER OF LEGES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
This paper deals with an important aspect of the legal-historical problem of the famous Theodosian Code (Codex Theodosianus / V century), as the first state codification of the Roman legal order of leges, whichis often unjustifiably in the research shadow of the later so-called Justinian's codification (Corpus Iuris Civilis Romani / VI century). More specifically, the author makes an attempt to shed light on a series ofsignificant issues of ‘legal romanistic’ from the late Roman or early Byzantine period, that refer to: theimportance, the meaning, the way of creation, the language, the structure, the way of citation, the territorialvalidity and the transcripts/manuscripts of the pre-Justinian codification of the laws passed by the so-called"Christian emperors", and created during the Eastern Roman Emperor Theodosius II. Among other things,from the point of view of the content, it is interesting that for the first time all the available titles of all 16books of the Codex have been translated from Latin into the Macedonian language! Towards the end of thepaper, the author makes a pioneering attempt, again for the first time in the Macedonian language, tointegrally translate the Decision of the Senate of the City of Rome on the Publication of the Theodosian Codex (lat. Gesta Senatus Romani de Theodosiano publicando / 438), as well as the Imperial Constitution about the constitutionaries (Constitutio de constitutionariis / 442) – which are considered as a kind ofintroduction, i.e. preface or preamble to the Codex of Theodosius.